Changes in DNA methylation patterns and repetitive sequences in blood lymphocytes of aged horses - Wnuk, Maciej (Springer Netherlands, 2013)
It is known that aged organisms have modified epigenomes. Epigenetic modifications, such as changes in global and locus-specific DNA methylation, and histone modifications are suspected to play an important role in cancer development and aging. In the present study, with the well-established horse aging model, we showed the global loss of DNA methylation in blood lymphocytes during juvenile-to-aged period. Additionally, we tested a pattern of DNA methylation of ribosomal DNA and selected genes such as IGF2 and found no significant changes during development and aging. We asked if genetic components such as polymorphisms within DNA methyltransferase genes, DNMT1, DNMT3a, and DNMT3b, may contribute to observed changes in global DNA methylation status. The analysis of seven intragenic polymorphisms did not reveal any significant association with changes in global DNA methylation. Telomere shortage and a loss of pericentromeric heterochromatin during juvenile-to-aged period were also observed. Transcriptional rDNA activity, assessed as the number and size of nucleolar organizer regions, reflecting physiological state of the cell, and mitotic index were decreased with increasing horse donor age. Moreover, changes during juvenile-to-aged period and adult-to-aged period were compared and discussed. Taken together, changes in global DNA methylation status originating in development and affecting the stability of repetitive sequences may be associated with previously reported genomic instability during horse aging.